Relação entre tópico discursivo e sequência argumentativa para a elaboração de um projeto de texto - Silva, Roberta Francisca Araújo da (2020)
The study of the argumentative text at school is still a practice related to high school, especially when it is associated with the genre redação do ENEM. Because of this, students arrive at high school without the ability to construct more efficient argumentative texts. With the intention of taking the student to high school with the ability to produce argumentative text, this work, whose subjects are 9th grade students from a public school in Ceará, proposes a sequence of activities that lead the student to invest in the discursive topic in order to confirm and expand the thesis and arguments in their texts. This work investigated how the properties of the discursive topic contribute to the delimitation of the thesis and arguments, providing the student with the elaboration of a text that implicitly demonstrates the development of a text project. Taking into account that argumentation is present in several situations in our life, it was intended, with the work proposed here, to provide students with activities through which they could develop the ability to produce argumentative texts since elementary school. This work mainly focused on the conceptions of Jubran (1996; 2006), Adam (2019), Amossy (2011; 2020); Sá (2018), Abaurre (2012), Cavalcante (2012), Cavalcante et. al (2007, 2017), Cavalcante and Paulinikonis (2018), koch (1991, 2004, 2011) Kock and Elias (2012, 2016, 2017) Oliveira (2016). The results achieved demonstrate that the activities involving the properties of the discursive topic collaborated to guarantee the approach, maintenance and thematic progression of the texts produced by the students. In this perspective, this research is justified by the relevance of the theme for teaching textual production and favors reflections about the ability to argue, developing students' critical sense.